The Most Frequency Chief Complaint of 5.5-12.5 Years Old Patients Attending POP Department of Hawler Medical University- College of Dentistry - Manal M. Taher; Yara I. Ameen (Erbil Dental Journal)
Background and objective: The chief complaints of the patients are important component during taking the history and treatment planning, be useful for several reasons including monitoring of oral health services and measuring the effectiveness of oral health awareness programs. the aim of the study to evaluate and address the most common chief complaints among a patients attending College of Dentistry at Hawler Medical University in Erbil, Iraq.